DECIPHERING THE DETERMINATION OF INDEX SHARIA FINANCIAL INCLUSION IN THE INDONESIAN LANDSCAPE - Arifin, Samsul; Rusgianto, Sulistya; Suprayitno, Aryadimas; Sholikah, Nia Mariatus (UPT Penerbitan Universitas Jember, 2024)
This research aims to provide an in-depth review of the literature on the Index Sharia Financial Inclusion (ISFI) and examine the determinants influencing it. The study employs a quantitative approach across 28 provinces in Indonesia. The ISFI value is calculated using a well-established formula referenced in prior studies. The methodology adopted is a widely recognized one, utilizing the EViews 10 software for analysis. The results indicate that two variables, GDP per Capita and the Human Development Index (HDI), have a significant positive impact on ISFI. Conversely, the Number of Poor Population and the Gini Ratio exhibit a significant negative effect. Additionally, Unemployment and Zakat Distribution in the economic sector do not show a significant impact. The findings of this research are intended to serve as a reference for evaluating and enhancing sharia financial inclusion in Indonesia.